Aplikasi Reservasi Transportasi Untuk Antar Jemput Karyawan di Kawasan PT. Pupuk Kujang Cikampek - Rafli Rasyidin; Kamal Prihandani; Oman Komarudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Pupuk Kujang Cikampek is a subsidiary of BUMN company, namely PT. Pupuk Indonesia Holding Company, which is engaged in the fertilizer industry. It has 34 departments and operates on an area of ​​510 hectares. With such a large area, traveling within the area will certainly be difficult if you do not have adequate vehicles or transportation. The Department of Public Services which is responsible for dealing with transportation service problems has a service in dealing with these problems, called Jajap. In simple terms, Jajap is a service to shuttle employees around the internal area of ​​PT. Pupuk Kujang Cikampek uses a car. Unfortunately, the Jajap service reservation method is still done conventionally and is considered inefficient in terms of time and energy for employees. Because employees are required to visit the vehicle pool location if they don't have a WA driver contact. So these problems need a system that can handle it. The purpose of this research is to design and develop a transportation reservation application for shuttle employees at PT. Pupuk Kujang Cikampek uses the Extreme Programming application development method. In developing the application. The results of the System Usability Scale test on the developed application show that the application can be accepted by users with the category of "Good" assessment interpretation with a score for the Jajap requestor application is 72, 125 and the score for the Jajap driver application is 74, 2.